1999
DOI: 10.1038/sj.onc.1203134
|View full text |Cite
|
Sign up to set email alerts
|

HPV-18 E6*I protein modulates the E6-directed degradation of p53 by binding to full-length HPV-18 E6

Abstract: We have previously demonstrated that ectopic expression of the HPV-18 E6*I protein has an antiproliferative e ect in cells derived from HPV-containing cervical tumours. This e ect correlated with the ability of E6*I to inhibit the E6-mediated degradation of p53 both in vitro and in vivo and with an increase in p53 transcriptional trans-activation. The observation that the E6*I protein can interact with both full-length HPV-18 E6 and E6-AP proteins in vitro indicated the mechanism by which this activity was med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
71
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 26 publications
7
71
0
2
Order By: Relevance
“…Nonetheless, decreased E6 levels can be deduced from enhanced p53 stabilization (Fig. 1B), which is consistent with the finding that E6* can counteract full-length E6-mediated p53 degradation (11).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nonetheless, decreased E6 levels can be deduced from enhanced p53 stabilization (Fig. 1B), which is consistent with the finding that E6* can counteract full-length E6-mediated p53 degradation (11).…”
Section: Discussionsupporting
confidence: 77%
“…The 8-kDa E6* protein was shown to modulate E6 functions. Studies show that HPV18 E6* can counteract E6 protein functions by rescuing p53 levels in vivo (11). Furthermore, though interaction of HPV16 E6 with procaspase-8 accelerates its degradation, binding of E6* results in procaspase-8 stabilization and therefore may sensitize the cells to tumor necrosis factor-alpha (TNFα)-mediated apoptosis (12).…”
mentioning
confidence: 99%
“…6,24) In most cervical cancers, the function of p53 is down-regulated by the E6 protein of HPV 16; E6 binds to p53 and leads to degradation of E6-p53 complexes. [10][11][12] Exogenous p53 overexpression results in degradation of viral E6 proteins and decreases the survival of cancer cells. 25) A previous study also showed that p53 binds E6 oncoprotein to decrease the tumorigenic properties of E6.…”
Section: Discussionmentioning
confidence: 99%
“…9) In most cervical cancers, however, the function of p53 is down-regulated by the E6 protein of HPV 16, whereby E6 binds to p53, resulting in degradation of E6-p53 complexes through the ubiquitin pathway. [10][11][12] For instance, human cervical cancer cell lines, such as CaSki (HPV 16), SiHa (HPV 16), HeLa (HPV 18) and HeLaS3 (HPV 18) express intact p53 protein. However, the viral E6 protein is required for the continuous growth of HPV-immortalized cells, in which E6 reduces the level of p53 protein, resulting in loss of G 1 arrest.…”
mentioning
confidence: 99%
“…Moreover, ectopic expression of the HPV-18 E6*I protein was found to have an antiproliferative effect in cell lines derived from cervical tumors. 18,19 These results led us to further examine the modulatory effects of E6*I on E6. Because no information is available on the patterns of expression of E6*I, we have used epitope-tagged versions of both HPV-18 E6 and HPV-18 E6*I to investigate their respective subcellular distribution.…”
mentioning
confidence: 99%